PENGUKURAN TINGKAT KECEMASAN MAHASISWA DALAM MENGHADAPI SKRIPSI DENGAN PENDEKATAN FUZZY INFRENCE SYSTEM MAMDANI - Susanto, Arif; Sunoto, Imam (Universitas Indraprasta PGRI, 2016)
Abstract: Conditions are less supportive of the event that is being experienced by a person, would cause an unpleasant feeling in that person. Feeling unpleasant and very disturbing soul and the mind can affect the meaning of students to events or issues that are being faced as the thesis work. Usuallymeaning that occurs almost always less subjective and can include public opinion because of the mind and heart are in an unstable state. Anxiety is an unpleasant feeling that is characterized by terms such as anxiety, concern and fear unexplained, experienced in different levels of the situation which is considered threatening. Anxiety is a feeling of fear and dread highly about something that will happen about the threats or actual difficulties vague and unrealistic that will arise in the future but it is not clear, and may endanger the welfare of a person. Anxiety can be both physically and psychologically. Measuring the level of anxiety in the face of thesis students can use fuzzy logicmamdani as a means of measurement. After calculation and experiment, the results of the determination didapatlah anxiety conditions faced by applying fuzzy mamdani with matlab. With the use of fuzzy logic levels of anxiety experienced can be identified quickly.Keyword: Anxiety, fuzzy, thesis, students